Implementation Implementation of Technology Acceptance Model and DeLone & McLean Model for ChatGPT User Acceptance - Saputra, Jefri Prayitno Bangkit; Waluyo, Retno; septi fajarwati; Hani, Nurul (Jurnal Pendidikan Edutama, 2025)
The learning style approach significantly impacts education, particularly in the Education 4.0 era, where both educators and institutions must innovate to enhance student outcomes. This study explores the use of artificial intelligence, particularly ChatGPT, in education. It integrates the Technology Acceptance Model (TAM) and DeLone & McLean models to examine how System Quality, Information Quality, and Service Quality influence Perceived Usefulness, Perceived Ease of Use, and technology acceptance. Data from 100 respondents analyzed using SmartPLS shows that System, Information, and Service Quality positively affect Perceived Usefulness and Perceived Ease of Use. Service Quality, however, does not influence Perceived Ease of Use. Perceived Usefulness and Ease of Use positively affect Attitude Toward Using, which in turn influences Behavioral Intention to Use. Finally, Behavioral Intention positively impacts Actual System Use. The model achieved an accuracy of 54.9%.